Blame Attributions Against Heterosexual Male Victims of Sexual Coercion: Effects of Gender, Social Influence, and Perceptions of Distress - Catton, Ashley K. H.; Dorahy, Martin J. (Journal of interpersonal violence, 2022)
If heterosexual male victims had been more active in the #MeToo movement, how might they have been judged? Although the #MeToo movement has been regarded as an historic milestone for women who were victimized by men in positions of power, participation in the movement by male victims has been noticeably absent. Research indicates that victims may avoid disclosure if they anticipate negative social reactions, and male victims may attract greater levels of victim blaming than female victims, particularly if their perpetrator was female. The current study investigated attributions of victim blame against a fictional heterosexual male in a between-subjects vignette design. Perpetrator gender and their social influence were manipulated in a sample of 208 college students. Results did not support the hypothesized main effects of perpetrator gender or social influence. Greater blame attributions were made against victims of a male perpetrator compared to one of an unspecified gender. Male participants attributed greater blame than females, and the relationship between shame proneness and blame was moderated by participant gender, males experiencing higher levels of shame engaged in less victim blame. Blame increased when participants believed the court case to be more distressing than the victimizing act. Results support the male rape myth framework, which posits that beliefs about a male victim’s experience of his own violation, particularly whether he experienced distress or pleasure, are related to gendered norms of masculinity, which include normative traits of toughness, dominance, and high sexual performance. Implications on the role of gender as a barrier to disclosure by male victims are discussed.